Neo-Poetic Film and its Representation of Ukraine’s Intangible Cultural Heritage - Zubavina, Iryna (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2023)
I look at Ukrainian neo-poetic film and its relationship with ICH, exploring the efforts to renew approaches to achieve filmic expressions of independence, “Ukrainian-ness,” and grounded-ness in the national aspect. To articulate the renewal of aesthetic and stylistic solutions for neo-poetic works in the 21st century, I first review the principles characteristic for the classics of Ukrainian poetic cinema of the 1960s. Based on an interest in folklore, ancient traditions, authentic details of daily life, the poetic cinema of the “Sixtiers” (шістдесятники) was saturated with deeply ambiguous content and engaged in poeticization and mythologization. This approach resonated with the later conceptualization of the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage. From the beginning of the 2000s, we see a change in approach in cinematic techniques for the re-creation of myths, rituals, aesthetic expressions of everyday life, and colourful ethnographic elements of Ukrainian culture. The film itself (beyond the physical medium) becomes (in)tangible cultural heritage.